Pendampingan Kewirausahaan bagi Pelaku UMKM di Kelurahan Jakamulya Kota Bekasi - Ria, Ria; Digdowiseiso, Kumba (LP2M INSURI Ponorogo, 2023)
The real performance faced by most businesses, especially micro, small, and medium enterprises (MSMEs) in Indonesia, which is most prominent is the low level of productivity, low added value and low product quality. Among the various contributing factors, the low level of mastery of technology and entrepreneurial skills among MSMEs is the issue that is currently surfacing. Therefore, the objectives to be achieved through entrepreneurship training activities for MSME actors in the Jakamulya Village, Bekasi City are to develop and enhance the entrepreneurial spirit of MSME actors, and increase marketing management knowledge of MSME actors. Among the various contributing factors, the low level of mastery of technology and entrepreneurial skills among MSMEs is the issue that is currently surfacing. Partial MSME development so far has not provided maximum results for improving MSME performance.